Preparation of KNiMo-based catalysts by using non-thermal plasma and their catalytic performance in the synthesis of higher alcohols from syngas - LI, Ying; ZHAO, Lu; LIU, Xiao-zhan; ZENG, Chun-xin; FANG, Ke-gong (Journal of fuel chemistry and technology, 2019)
A series of KNiMo-based catalysts were prepared by using non-thermal plasma and characterized by XRD, nitrogen sorption, TEM, H2-TPD, CO-TPD, and in-situ CO adsorption DRIFTS; their catalytic performance in the higher alcohol synthesis (HAS) from syngas was investigated. The results indicate that in comparison with those prepared by the conventional thermal method, the KNiMo-based catalysts prepared by using non-thermal plasma display thinner and shorter MoS2 slabs and more highly dispersed and coordinatively unsaturated sites, which endow the KNiMo-based catalysts excellent performance in HAS. In particular, for the HAS over the KNiMo-DPS catalyst under 350°C, 5 MPa, and a gas hourly space velocity (GHSV) of 5000 h−1, the conversion of CO reaches 32.3%, with a selectivity of 75.1% to total alcohol and a C2+ alcohol selectivity of 65.2% in the total alcohols.